2017
DOI: 10.1249/mss.0000000000001184
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenergic Responsiveness in the Type 2 Diabetic Heart

Abstract: Although the type 2 diabetic heart worked at smaller volumes, the HR and contractile response to β-adrenergic stimulation were unaffected by diabetes. The reduced cardiac reserve observed in uncomplicated T2D was not explained by impaired myocardial sympathetic responsiveness but may reflect changes in the loading conditions or function of the diabetic left ventricle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Wilson et al [ 35 , 36 ] recently reported an almost identical reduction in HR reserve in T2DM subjects as compared with control subjects. They investigated whether this may be attributable to reduced β-adrenoreceptor sensitivity.…”
Section: Discussionmentioning
confidence: 97%
“…Wilson et al [ 35 , 36 ] recently reported an almost identical reduction in HR reserve in T2DM subjects as compared with control subjects. They investigated whether this may be attributable to reduced β-adrenoreceptor sensitivity.…”
Section: Discussionmentioning
confidence: 97%
“…In addition tempered vasodilator responses of the vascular smooth muscle elicited subsequent to exogenous, direct-acting nitric oxide (NO) donors in the form of glyceryl trinitrate (McVeigh et al, 1992) and sodium nitroprusside (Kingwell et al, 2003;Williams et al, 1996) have also been reported in the respective T2D cohorts. It is pertinent to acknowledge, however, that in the absence of cardiac output (CO) data, we cannot exclude the possibility that impairments in cardiac function (Joshi et al, 2010;Regensteiner et al, 2009;Wilson et al, 2017a;Wilson et al, 2017b) could induce subsequent regional O2 delivery impediments; although peak CO is not significantly reduced in uncomplicated T2D (Baldi et al, 2003;Regensteiner et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Peterson et al [ 15 ] found that resting early diastolic filling was inversely proportional to exercising stroke volume in healthy older people, suggesting that resting measurements of diastolic function have an arbitrary relationship with LV filling during exercise. In contrast, LV contractile responses to β-adrenergic stimulation are often [ 29 33 ] but not always [ 34 ] reduced in the diabetic heart, providing evidence that impaired systolic responses during exercise could limit cardiac reserve. In addition, a recent paper found that end diastolic volume responses to exercise were blunted, but end systolic volume responses were unchanged in adolescents with type 1 diabetes during supine exercise [ 35 ].…”
Section: Discussionmentioning
confidence: 99%